2012
DOI: 10.1140/epje/i2012-12007-0
|View full text |Cite
|
Sign up to set email alerts
|

The scaling and dynamics of a projectile obliquely impacting a granular medium

Abstract: Abstract. In this paper, the dynamics of a spherical projectile obliquely impacting into a two-dimensional granular bed is numerically investigated using the discrete element method. The influences of projectile's initial velocities and impacting angles are mainly considered. Numerical results show that the relationship between the final penetration depth and the initial impact velocity is very similar to that in the verticalimpact case. However, the dependence of the stopping time on the impact velocity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…The size distribution of particles is very similar to that used in an existing physical experiment [6], in order to directly validate our simulation method. It has been confirmed that the scaling of penetration depth is almost independent of the choice of system parameters if the variation of packing fraction induced by size distribution is small [33]. The method of generating targets has significant influence on the final material [36], which is mainly for cohesive aggregation, but also for some noncohesive cases.…”
Section: Model and Methodsmentioning
confidence: 88%
See 3 more Smart Citations
“…The size distribution of particles is very similar to that used in an existing physical experiment [6], in order to directly validate our simulation method. It has been confirmed that the scaling of penetration depth is almost independent of the choice of system parameters if the variation of packing fraction induced by size distribution is small [33]. The method of generating targets has significant influence on the final material [36], which is mainly for cohesive aggregation, but also for some noncohesive cases.…”
Section: Model and Methodsmentioning
confidence: 88%
“…We establish a simulating model substantially similar to the previously proposed model [33], and its effectiveness has been evaluated carefully. Since the positions and forces of individual particles are conveniently traced in a DEM simulation, the influences of particle rotation on the entire dynamical process can be quantitatively examined by analyzing the evolution of velocity field and the trajectories of projectiles for oblique impact.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The formation of impact craters due to the penetration of projectile into granular media has been studied comprehensively [4,[11][12][13][14][15]. The influence of confinement on the penetration depth was studied experimentally [16][17].…”
Section: Introductionmentioning
confidence: 99%